NEIGHBORHOOD GREENNESS AND CHRONIC KIDNEY DISEASE, AMONG 249,405 U.S. MEDICARE BENEFICIARIES - William W. Aitken, MD (Elsevier, 2024)
Therapeutic Area: Kidney Disease Background: Neighborhood greenness has been linked to higher levels of physical activity and improved health outcomes, including cardiometabolic conditions (e.g., hyperlipidemia, diabetes) and cardiovascular disease. The relationship of greenness to chronic kidney disease has been less studied. Understanding the role of environmental factors in chronic kidney disease in older adults may inform and complement traditional interventions for Cardiovascular-Kidney-Metabolic health, including primary and secondary prevention. Methods: This research examined data from 249,405 U.S. Medicare beneficiaries, ages>65 years living in the same location in Miami-Dade County across two calendar years (2010-2011). Multilevel analyses assessed the relationship between neighborhood greenness, assessed by mean block-level Normalized Difference Vegetative Index (NDVI) via satellite imagery, and chronic kidney disease diagnosis using Medicare claims data. Covariates were individual age, gender, race/ ethnicity, number of cardiometabolic conditions, and neighborhood median household income. Results: Higher levels of neighborhood greenness (NDVI) were associated with lower odds of chronic kidney disease (CKD). Compared to individuals residing in the lowest tertile of greenness, those individuals residing in the highest tertile of greenness had a 14% lower odds of CKD (OR=0.86; 95% CI: 0.81, 0.91, p<0.0001). This relationship remained statistically significant after adjusting for age, gender, race/ethnicity, and neighborhood income (OR=0.77; 95% CI: 0.68, 0.87, p<0.0001). Conclusions: Neighborhood greenness, which has previously been linked to greater physical activity opportunities and improved health may also reduce risk of CKD in older adults, and contribute to Cardiovascular-Kidney-Metabolic health.